Potential vorticity structure of embedded convection in a warm conveyor belt and its relevance for large-scale dynamics ... - Oertel, Annika; Boettcher, Maxi; Joos, Hanna; Sprenger, Michael; Wernli, Heini (ETH Zurich, 2020)
Warm conveyor belts (WCBs) are important airstreams in extratropical cyclones. They can influence large-scale flow evolution by modifying the potential vorticity (PV) distribution during their cross-isentropic ascent. Although WCBs are typically described as slantwise-ascending and stratiform-cloud-producing airstreams, recent studies identified convective activity embedded within the large-scale WCB cloud band. However, the impacts of this WCB-embedded convection have not been investigated in detail. In this study, we systematically analyze the influence of embedded convection in an eastern North Atlantic WCB on the cloud and precipitation structure, on the PV distribution, and on larger-scale flow. For this reason, we apply online trajectories in a high-resolution convection-permitting simulation and perform a composite analysis to compare quasi-vertically ascending convective WCB trajectories with typical slantwise-ascending WCB trajectories. We find that the convective WCB ascent leads to substantially ... : Weather and Climate Dynamics, 1 (1) ...